Assessment of the Performance of Various Hybrid Maize (Zea mays L.) Varieties During Spring Season in Dhading, Nepal - Ranjan Bhattarai; Mamata Kumari Neupane; Mukesh Pant; Subheksha Shrestha; Kalyani Mishra Tripathi (Turkish Journal of Agriculture: Food Science and Technology)
A field experiment was conducted at Nilkantha Municipality-12 Dhadingbesi, Dhading from March to July 2024, with a set of seven hybrid maize genotypes. Three replications of a RCBD were used to assess the genotypes and samples were taken for several characteristics like plant height, days to 50% plant emergence, days to 50% plant tasseling, days to 50% silking, anthesis-silking interval, cob height, leaf number, stem girth, number of cobs/plant, cob length, cob girth, number of kernel row/cob, number of kernel/row, test weight and grain yield. The highest days to the emergence of seedlings is Rampur Hybrid-8 (9.33 day) and the lowest days is C.P.808 (6.33 day). The plant height was significantly higher in Rampur Hybrid-10 (290.73 cm). Days to 50% tasseling and silking are relatively earlier in Rampur Hybrid-8 (63 day) and Rampur Hybrid-10 (65.33 day) respectively which is at par with C.P.808 and Anthesis-silking interval is comparatively lower in Rampur Hybrid-10 (1.33 day). Leaf number below the main cob was found higher in Rampur Hybrid-14 (9.30), whereas leaf above the main cob was found to be non-significant. Cob height was found to be lowest in C.P.808 (139.97 cm). Stem girth was found to be higher in C.P.808 (9.07 cm) followed by Rampur Hybrid-10 (8.38 cm). Similarly, Rampur Hybrid-14 had the most cobs per plant (1.53). Cob length and cob girth was found to be non-significant. Number of rows in a cob was higher in C.P.808 (16.33) followed by Rampur Hybrid-10 (15.97). Number of kernel/row was higher in C.P.808 (35.93) followed by Rampur Hybrid-12 (34.04). Similarly grain yield was higher in C.P.808 (10.44 Mt/ha) followed by Rampur Hybrid-10 (9.80 Mt/ha). Test weight was highest in Rampur Hybrid-10 (347.75 g). Looking at the performance of these varieties C.P.808 and Rampur Hybrid-10 can be recommended for the Dhading district.